Effect of Replacing Fish Oil with Palm Oil on Liver Histology and Nutritional Quality of Nile Tilapia (Oreochromis niloticus) - Ayisi, Christian Larbi; Zhao, Jin-Liang (Indian Journal of Animal Nutrition, 2018)
The effects of replacing fish oil (FO) with palm oil (PO) in diets of Nile tilapia (Oreochromis niloticus)were studied on liver morphology as well as nutritional quality. An eight week feeding trial was conducted using five iso-nitrogenous and iso-caloric diets containing 0, 25, 50, 75 and 100% PO in replacement of FO. Each diet was randomly assigned to triplicate groups of 40 fishes. After 8 weeks of feeding trial, the findings demonstrated that body composition as well as liver and muscle lipid were not affected by different PO levels in diets. However, there was an increase (P